Exploratory factor analysis of Kenny Music Performance Anxiety Inventory (K-MPAI) in a Brazilian musician sample (Archives of Clinical Psychiatry, 2015)
Background The Kenny Music Performance Anxiety Inventory (K-MPAI) is very significant among the available instruments which measures Musical Performance Anxiety (MPA). Objective The aim of this study is to find evidence of validity of the Kenny Music Performance Anxiety Inventory (K-MPAI), in its translated and adapted Brazilian version, through the study of its factor structure. Methods A convenience sample of 230 amateur musicians completed the K-MPAI. Results The initial factor analysis yielded eight factors, explaining 62.4% of variance. However, due to the factors’ composition and internal consistency values lower than 0.50, the number of factors was later set at three, considering the internal consistency of those, the theoretical propositions and symptomatology aspects that supported the construction of scale. They were named “Worries and insecurity” (α = 0.82), “Depression and hopelessness” (α = 0.77) and “Early parental relationships” (α = 0.57). Discussion/Conclusions These results point to the scale’s construct validity, since they support the theoretical basis used for the development of the K-MPAI and the clinical manifestations of the MPA.